INFERIORITAS PEREMPUAN DALAM BAHASA IKLAN BANNER SAFETY RIDING - Patria, Fedi Bhakti (Universitas Negeri Surabaya, 2015)
Women are still often imaged positively by the authorities in the public sphere. This can be seen from some of the elements contained in the images, including in the text